Sarcopenia in liver cirrhosis: perspectives from epigenetics and microbiota - Xu, Jia-qi; Pan, Yu-ke; Zhang, Jie-xin; Dai, Shi-xue; Xu, Li-shu (Frontiers in Medicine, 2023)
Sarcopenia is characterized by the loss of muscle mass and function. It is well known that sarcopenia is often associated with aging, while in recent years, sarcopenia comorbid with chronic diseases such as cirrhosis has attracted widespread attention, whose underlying molecular mechanisms remain unclear. Since cirrhosis and sarcopenia are assumed to be closely interrelated in terms of pathogenesis, this review innovatively discussed the role of epigenetic modifications and microecological dysregulation in sarcopenia in the context of liver cirrhosis. Here we illustrated the relationship between sarcopenia and cirrhosis in the aspect of epigenetics, dysbiosis, and the crosstalk between gene modifications and intestinal microecology. Furthermore, the alterations in cirrhosis patients with sarcopenia, such as inflammatory response and oxidative stress, are found to present synergistic effects in the pathways of epigenetics and dysbiosis leading to sarcopenia. This review proposes that microbiome-based therapies are promising to break the vicious cycle between epigenetic modification and dysbiosis, providing strong support for the use of intestinal microecological interventions to prevent sarcopenia in cirrhotic patients.